Kitab Ayyuhal Walad dan Nasehat-nasehat Imam Ghazali - Maulidi (IIQ An Nur Yogyakarta, 2022)
In the Islamic boarding school world, the study of turast books across disciplines is a tradition. The way of learning is also different. Starting from the talaqiy method, munawalah, to the polar bahstul method. In fact, when departing from Al-Ghazali's theory of the method of obtaining knowledge there are twofold: the kasbi theory (how to obtain knowledge scientifically and naturally) and the kasyfi theory (how to obtain knowledge by riyadlah and inner ritual). In the Islamic tradition, both are equally practised. However, the kasbi theory is most widely pursued because it is more likely, while the kasyfi theory is relatively impossible, not to say absurd.